2017
DOI: 10.1111/acer.13470
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Liver and Plasma in Chronic Ethanol Feeding Model of Hepatic Alcohol Dehydrogenase-Deficient Deer Mice

Abstract: Background Chronic alcohol abuse, a major risk factor for such diseases as hepatitis and cirrhosis, impairs hepatic alcohol dehydrogenase (ADH, key ethanol metabolizing enzyme). Therefore, differentially altered hepatic and plasma proteomes were identified in chronic ethanol feeding model of hepatic ADH-deficient (ADH−) deer mice to understand the metabolic basis of alcoholic liver disease (ALD). Methods ADH− deer mice were fed 3.5g% ethanol via Lieber-DeCarli liquid diet daily for three months, and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…It has been reported that ethanol favors hepatic steatosis, probably because of the increase of lipogenesis, diminution of lipid transport of the liver, alteration of oxygenation of fatty acids[ 27 ], and even infiltration of monocytes, macrophages, etc ., which are fundamental for pathogenic activity after acute or chronic hepatic injury[ 27 ]. The latter can explain in part the histological findings encountered in our study, where fatty change as well as inflammation comprised the most important changes in weekend alcohol consumption in all of the groups (Table 4 ), probably due to that they are related with the acute damage caused by ethanol to the liver[ 16 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ethanol favors hepatic steatosis, probably because of the increase of lipogenesis, diminution of lipid transport of the liver, alteration of oxygenation of fatty acids[ 27 ], and even infiltration of monocytes, macrophages, etc ., which are fundamental for pathogenic activity after acute or chronic hepatic injury[ 27 ]. The latter can explain in part the histological findings encountered in our study, where fatty change as well as inflammation comprised the most important changes in weekend alcohol consumption in all of the groups (Table 4 ), probably due to that they are related with the acute damage caused by ethanol to the liver[ 16 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Charles Lieber and Dr. Leonore DeCarli created a unique model by administering EtOH as part of a nutritionally complete liquid diet (Lieber and DeCarli, 1982 ). This consumption model has been the forerunner in the EtOH research field as a useful tool to study pathological disorders associated with AUD, such as alcoholic liver disease (Dolganiuc et al, 2009 ; Bhopale et al, 2017 ; Guo et al, 2018 ). Another commonly used exposure method is EtOH vapor inhalation which is useful to maintain constant, clinically relevant blood EtOH concentrations and to induce EtOH dependence (Healey et al, 2008 ; Snyder et al, 2019 ).…”
Section: Models Of High Fat Diet and Alcohol Intakementioning
confidence: 99%
“…The phosphorylation of histone is catalyzed by MAPK, largely in serine 10 and 28 of H3 after alcohol exposure and is generally related to transcriptional activation (Lee and Shukla, ). Acetyl‐CoA generated after alcohol metabolism can participate in the tricarboxylic acid cycle, which provides ATP or GTP, whose phosphate can further be transferred to N‐terminal amino acid residues under the mediation of MAPK (Bhopale et al., ). Different alcoholic drinking patterns have diverse effects on the epigenetic modification of histone.…”
Section: Histone Modification By Alcoholmentioning
confidence: 99%